Occupational Health and Safety: An expected learning outcome of Civil Engineering Graduates - Vimonsatit, Vanissorn; Nikraz, Ommid (Engineers Australia, 2011)
The high number of fatalities in the construction industry shows the needs for improvement in Occupational Health and Safety (OHS) measures. Civil Engineers, being regarded as a member of ‘top tier’ management in construction projects, are prone to have knowledge of OHS procedures and regulations. However, OHS training is not always integrated in engineering education. This paper identifies the need to incorporate the teaching and learning of OHS in Civil Engineering education, and proposes that the knowledge of OHS is an expected learning outcome of Civil Engineering graduates.Since 2010, The Department of Civil Engineering at Curtin University has recently incorporated OHS topics in a construction management unit of its undergraduate course. To test OHS awareness, pre- and post-lecture questions relating to the basic knowledge of OHS in construction practices, laws and legislations have been distributed to the students in a class of final year students. The answers to the pre-lecture questions are used as the key indication of the weakness and strength in the knowledge and the perception of the students regarding OHS in construction. The lecturer can also use thisinformation to deliver the lectures more effectively towards the expected learning outcome of the topics. The answers to the post-lecture questions provide excellent feedback on the teaching and learning effectiveness. This paper will present the analysis of the answers to the pre- and post-lecture questions based on the contents that are deemed necessary and important for the students to possess the basic knowledge, attributes and skills in OHS. The paper will also present how OHS, as an expectedlearning outcome of Civil Engineering graduates,will improve the relevance of engineering education for industrial practices.